Pemberdayaan Ibu Primigravida Melalui Upaya Promosi Kesehatan Untuk Deteksi Dini Pra Eklamsi Dalam Mengurangi Angka Kematian Ibu - Trisna Vitaliati (Jurnal Kesehatan dr. Soebandi, 2019)
Early detection related to classification or activities to obtain information about pregnant women is very helpful in preparing for the control of the risk of pregnancy complications. Although the occurrence of preeclampsia cannot be completely prevented, its frequency can be reduced by making early detection. Non-compliance of pregnant women in antenatal care can cause various pregnancy complications not to be known so that they are not immediately addressed, so a health promotion strategy is needed with community empowerment efforts in this case is primigravida mothers. This allows the community and health workers to take adequate care and succeed in reducing maternal mortality.This study aims to analyze the empowerment of primigravida mothers for early detection of preeclampsia in Jember Regency. The research method used was Quasi Experimental Design with Pre-Post Test Control Group Design. The sample in this study was taken probability / random by cluster random sampling technique. The analysis is done univariately and bivariately.The results showed the average score of behavior change in the intervention group and the control group. In the Mann Whitney test results obtained p-value <0.05 so it can be concluded that the empowerment of primigravida mother programs significantly influence behavioral changes in early detection of preeclampsia. Primigravida mother empowerment program is effective in increasing pre-eclampsia early detection behavior so that this program is suggested to be applied to pregnant women as part of maternal and child health programs.